MEKANISME PEMBAGIAN HARTA BERSAMA BERDASARKAN HUKUM ADAT DI DESA BAWOMATALUO SETELAH TERJADINYA PERCERAIAN - Wau, David Kristian (LPPM Universitas Nias Raya, 2025)
Humans were created in general by God that humans are actually living social creatures. interact with each other. Humans themselves cannot live their lives alone, they. still need other people, because in general every human being needs other human beings to live together. The smallest form of humans living together by forming a family. The research aims to find out and explain the mechanism for dividing joint assets based on customary law in Bawomataluo Village after a divorce occurs. The type of research used is sociological legal research. Sociological legal research is legal research in the form of empirical studies to discover the application and truth of law in society. The aim of sociological legal research is to find information about something that happened. The type of approach used is descriptive using initial data as a comparison. The data collection technique is library research. This research data analysis is a descriptive research specification, which means research that aims to describe research about something that is valid at a certain time. Based on the research findings and discussion in the research, the researcher can conclude that regarding the distribution of joint property which has been carried out according to customary law and is very clear. states that the distribution of assets is carried out equally, fairly and fairly, with each half of the share. Thus, both the sumai and the wife must carry out customary law decisions voluntarily. However, if both parties are not satisfied with the results of the decision regarding the division of joint assets, then both parties can file a lawsuit in court. State as a legal remedy because there is no agreement. With this, from the legal consequences that occur after. division of joint assets, after completing the division of assets, the legal consequence is that the joint assets will become legal and rightfully belong to each party. In this way, both the ex-husband and wife can use the item again.